Learning technical Spanish with virtual environments - Siebert, Caspian, author; Ortega, Francisco R., advisor; Miller De Rutté, Alyssia, committee member; Krishnaswamy, Nikhil, committee member (Colorado State University. Libraries, 2024)
As the world becomes increasingly interconnected through the internet and travel, foreign language learning is essential for accurate communication and a deeper appreciation of diverse cultures. This study explores the effectiveness of a virtual learning environment employing Artificial Intelligence (AI) designed to facilitate Spanish language acquisition among veterinary students in the context of diagnosing a pet. Students' engagement with virtual scenarios that simulate real-life veterinary consultations in Spanish is examined using a qualitative thematic analysis. Participants have conversations with a virtual pet owner, discussing symptoms, diagnosing conditions, and recommending treatments, all in Spanish. Data was collected through recorded interactions with the application and a semi-structured interview. Findings suggest that immersive virtual environments enhance user engagement and interest, and several suggestions were made to improve the application's features. The study highlights the potential for virtual simulations to bridge the gap between language learning and professional training in specialized fields such as veterinary medicine. Finally, a set of implications of design for future systems is provided.
Keywords: educational technology; task-based learning; virtual environments; language learning; artificial intelligence; veterinary medicine